2008
DOI: 10.1177/1049732308329309
|View full text |Cite
|
Sign up to set email alerts
|

The Encounter Between Informal and Professional Care at the End of Life

Abstract: The purpose of this study was to obtain and describe in-depth knowledge about family carers' experiences of the encounter, in a hospital, between informal and professional care at the end of life. A hermeneutic approach was chosen, and we conducted interviews with 27 family carers 6 to 8 months after their loved one's death. In the encounter, the family carers made their own assessment of their loved one's condition and situation. The professionals' attitudes could both promote and impede the interaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
(56 reference statements)
3
33
0
2
Order By: Relevance
“…This result suggests that the entire sample believes that the spouses or most involved family caregivers of people with dementia know best what the real needs of these persons are, and what care is the best, or least harmful, for them. This finding is congruent with those of James (2009) showing family caregivers' actions as protecting their loved one's interests. Yet, the spouses' age and often poor health raises some doubts regarding the spouses' capacity to make difficult decisions in end-oflife issues (Lautrette et al, 2006).…”
Section: Aging and Mental Health 81supporting
confidence: 93%
“…This result suggests that the entire sample believes that the spouses or most involved family caregivers of people with dementia know best what the real needs of these persons are, and what care is the best, or least harmful, for them. This finding is congruent with those of James (2009) showing family caregivers' actions as protecting their loved one's interests. Yet, the spouses' age and often poor health raises some doubts regarding the spouses' capacity to make difficult decisions in end-oflife issues (Lautrette et al, 2006).…”
Section: Aging and Mental Health 81supporting
confidence: 93%
“…The patient has the primary understanding about the mood of unhomelikeness which is the actual matter of the encounter (Svenaeus, 2000a). In a study about encounters between formal and informal care at the end of life, James, Andershed, and Ternestedt (2009) suggested that informal care performed by loved ones can be understood as a kind of practical knowledge, linked to Aristotle's phronesis, that is complementary to medical expertise. In the context of our study, the participants' lived experiences of IBS can be translated to practical knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Such comfort is created in the essence of the encounter between professionals and the family facing the end-of-life experience of one of its members, permeated by the emotional involvement and the ability of professionals' identification with the family (James et al, 2009). This encounter between the professionals and the patient´s family happens by means of social interactions, essential to the process of caring for end-of-life elderly´s families.…”
Section: Discussionmentioning
confidence: 99%